Adaptasi cerpen Chuumon no Ooi Ryouri Ten karya Miyazawa Kenji menjadi anime Karya Shibuichi Setsuko - Noviana, Fajria (Japanese Research on Linguistics, Literature, and Culture, 2018)
This paper is the result of a qualitative descriptive type of literature study. The purpose of this study was to describe what changes Shibuichi Setsuko made in the Chuumon no Ooi Ryouri Ten anime as an adaptation work from Miyazawa Kenji's children's short story with the same title. In addition, it also describes what pedagogical values are contained in this adaptation work. The method used is a comparative method to compare the anime version of the Chuumon no Ooi Ryouri Ten narrative with the short story intrinsic element. Meanwhile, based on the four main points of teaching Seikatsuka or life environment studies that applied in Japanese elementary schools, pedagogical values of this anime can be reveal. As a result of the analysis of Shibuichi Setsuko's creative adaptation, four changes were found in the anime version. The four changes lie in the number of characters, characterizations, plot stages, and location setting. Whereas as a result of the analysis of pedagogical values, it is known that this anime fulfills the four main points of the Seikatsuka. This is parallel with Altman's assumption about children's films which suggest that children's film viewers are expected to get teaching, morality, and understanding of identity as a pedagogical experience to improve the quality of life from what they watch.Â Keywords: adaptation, anime, children's short stories, pedagogical values